2019
DOI: 10.1021/acs.est.9b02452
|View full text |Cite
|
Sign up to set email alerts
|

Traces of a Neonicotinoid Induce Precocious Foraging and Reduce Foraging Performance in Honey Bees

Abstract: There is increasing worldwide concern about the impacts of pesticide residues on honey bees and bee colony survival, but how sublethal effects of pesticides on bees might cause colony failure remains highly controversial, with field data giving very mixed results. To explore how trace levels of the neonicotinoid pesticide imidacloprid impacted colony foraging performance, we equipped bees with RFID tags that allowed us to track their lifetime flight behavior. One group of bees was exposed to a trace concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 90 publications
0
97
2
2
Order By: Relevance
“…This may be surprising, as our bees were fed with IMD, particularly in the bees fed during the preimaginal stages, though Colin et al (2019) revealed that IMD delivered only during the larval stage strongly influences worker foraging. This requires further study.…”
Section: Queensmentioning
confidence: 86%
See 2 more Smart Citations
“…This may be surprising, as our bees were fed with IMD, particularly in the bees fed during the preimaginal stages, though Colin et al (2019) revealed that IMD delivered only during the larval stage strongly influences worker foraging. This requires further study.…”
Section: Queensmentioning
confidence: 86%
“…Imidacloprid (IMD) is a widely used neonicotinoid insecticide in agriculture (Simon-Delso et al 2015). Sublethal doses of neonicotinoids impaired larval development, gland and neurobiological functions (Blacquière et al 2012;Henry et al 2015;Mužinić and Želježić 2018), longevity, resistance to biotic and abiotic stress (Van der Sluijs et al 2013;Dively et al 2015), foraging, and orientation (Colin et al 2019;Jacob et al 2019) in honeybee workers. IMD also increased the replacement rate, impaired reproductive traits, decreased body weight in queens (Williams et al 2015;Chaimanee et al 2016), and handicapped the sperm quality of drones (Ciereszko et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune competence has been shown to be compromised in starved social insects [153,175], stressing the energetic costs involved in mounting an immune response [176]. Thus, reduced foraging performance due to stress-induced impaired cognitive abilities may trigger a cascade of food shortage when lower quantities or quality of resources are collected [20,174,177], or alter the social networks of nursing individuals and impair thermoregulation [43]. The disruption of social networks may also translate into altered grooming behavior, which may increase the susceptibility to pathogens breaking through the barrier of the cuticle, such as fungal entomopathogens, as spores are no longer removed from a nestmate´s cuticle [178].…”
Section: Pollutants and Disease Susceptibility Of Social Insects-mechmentioning
confidence: 99%
“…Sublethal health effects can translate into more dramatic effects, for example by increasing disease susceptibility [4,[7][8][9][10][11][12][13] or decreasing tolerance towards other stressors, such as land use intensification [14][15][16][17]. In addition, such pollutants are known to negatively affect learning abilities and/or lower activity levels [18][19][20][21][22][23][24], which may compromise insects even further [19,21,25].…”
Section: Introductionmentioning
confidence: 99%